Presence of Extended-Spectrum β-lactamase, CTX-M-65 in Salmonella enterica serovar Infantis Isolated from Children with Diarrhea in Lima, Peru - Granda, Ana; Riveros, Maribel; Martínez-Puchol, Sandra; Ocampo, Karen; Laureano-Adame, Laura; Corujo, Alfredo; Reyes, Isabel; Ruiz, Joaquim; Ochoa, Theresa J. (Journal of Pediatric Infectious Diseases, 2019)
Gastroenteritis in children is a serious condition in many parts of the world. Salmonella enterica is one of the causes of the disease. In this study, 280 fecal samples from children with diarrhea in four hospitals in Lima, Peru, were collected between September 2012 and March 2013. Salmonella was detected in 26 of the samples. Serotyping demonstrated that 25 of the isolates were S. enterica Infantis, and one isolate was S. enterica Typhimurium. Repetitive extragenic palindromic–polymerase chain reaction analysis suggests that all S. Infantis belong to the same clone. All but one of the S. Infantis isolates exhibited an extended-spectrum β-lactamase phenotype as they harbored blaCTX-M 65. Two strains also carried blaTEM-1. Nine of the isolates were resistant to azithromycin and two to ciprofloxacin. This study demonstrates that a multidrug-resistant S. Infantis clone carrying blaCTX-M 65 was circulating among children in Lima, Peru. The development of molecular epidemiology studies in Salmonella-causing diarrhea or other pathologies in Lima and in other areas will be useful to determine the permanence, geographical spread, and clinical implications of this clone.
Keywords: extended-spectrum β-lactamases; Salmonella enterica serovar Infantis; diarrhea